An Evidence-based Psychotherapy for Bipolar Disorder in Community Mental Health Settings: Facilitators and Barriers to IPSRT Implementation - Stein, Bradley D. (2013)
OBJECTIVE: Despite widespread use of individual outpatient psychotherapies in community mental health clinics (CMHCs), few studies have examined implementation of these psychotherapies. This exploratory qualitative study identified key themes associated with the implementation of an empirically supported psychotherapy in CMHCs. METHODS: We conducted semi-structured interviews with twelve key informants from four CMHCs trained in interpersonal and social rhythm therapy (IPSRT) and categorized recurring key themes. RESULTS: Five major themes were identified: pre- training familiarity with IPSRT, administrative and management support, IPSRT “fit” with usual practice and clinic culture, implementation team and plan, and supervision and consultation. Discussion of these themes varied between participants from clinics that had successfully implemented IPSRT and those that had not. CONCLUSIONS: Interviewees identified both key themes and several strategies for facilitating implementation. Our findings suggest that when these key factors are present, outcome-enhancing treatments can be implemented and sustained, even in clinics with limited resources.